Orthodontic Treatment of a Bilateral Mandibular Lateral Incisor-Canine Transposition - Alev Yılmaz; Zahire Şahinoğlu (Galenos Yayinevi, 2012)
Transposition is a form of ectopia, in which two adjacent teeth change positions in the dental arch. It can be partial or complete. Transpositions are a challenge to orthodontics, especially if treatment aims to correct the order of the teeth. The aim of this case report was to present the treatment of a patient who had bilaterally transposed mandibular lateral incisor and canine teeth.